Should optimal timing between two intrauterine transfusions be based on estimated daily decrease of hemoglobin or on measurement of fetal middle cerebral artery peak systolic velocity?. Issue 4 (14th March 2017) - Ghesquière, Louise; Houfflin‐Debarge, Véronique; Behal, Hélène; Coulon, Capucine; Subtil, Damien; Vaast, Pascal; Garabedian, Charles
Abstract : BACKGROUND: To best predict the recurrence of fetal anemia after intrauterine transfusion (IUT), the measurement of middle cerebral artery peak systolic velocity (PSV) and the estimation of hemoglobin (Hb) daily decrease are compared. STUDY DESIGN AND METHODS: A retrospective study including 38 patients who had at least two IUTs in a context of red blood cell alloimmunization was conducted. PSV values before first, second, and third IUTs were collected and expected Hb level was calculated according to various Hb daily decrease formulas as proposed in the literature. RESULTS: Comparison of PSV receiver operating characteristic curves with the various Hb levels did not find any significant difference between first and second IUTs. On the other hand, we found a significant difference between the second and third IUTs, with better prediction of fetal anemia through Hb decrease calculation, whatever the formula. Between the second and third IUTs, no formula was significantly better than the others. CONCLUSION: The timing of a second transfusion can be difficult to determine with certainty, but PSV can give an accurate assessment of when to resample the fetus with probably a higher recommended threshold for the diagnosis of fetal anemia. Subsequent to a second transfusion, the intertransfusion interval should be based on estimated Hb decrease rather than PSV thresholds, whatever the chosen formula proposed in the literature. Larger numbers are needed to definitely make this recommendation and it will be interesting to evaluate correlation between different antibodies.